2003
DOI: 10.1044/1092-4388(2003/103)
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Language Abilities in Adolescents With Down Syndrome and Children With Specific Language Impairment

Abstract: This article compared the language profiles of adolescents with Down syndrome (DS) and children with specific language impairment matched for nonverbal cognitive ability, and investigated whether similar relationships could be established between language measures and other capacities in both groups. Language profiles were very similar: Expressive language was more affected than language comprehension, and grammar was more affected than vocabulary in both domains. Both groups were impaired on tests of grammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
191
2
21

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(230 citation statements)
references
References 54 publications
16
191
2
21
Order By: Relevance
“…Buckley (1993) found that children with Down syndrome were more accurate at learning spoken sentences when they had previously seen the written form of the sentence. As both morphology and syntax are particular weaknesses for children with Down syndrome (Laws & Bishop, 2003), it is possible that orthography may benefit the grammatical learning of children with Down syndrome more than typically developing children. Furthermore, this study could be carried out with children with Down syndrome with lower levels of reading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buckley (1993) found that children with Down syndrome were more accurate at learning spoken sentences when they had previously seen the written form of the sentence. As both morphology and syntax are particular weaknesses for children with Down syndrome (Laws & Bishop, 2003), it is possible that orthography may benefit the grammatical learning of children with Down syndrome more than typically developing children. Furthermore, this study could be carried out with children with Down syndrome with lower levels of reading.…”
Section: Discussionmentioning
confidence: 99%
“…Children with Down syndrome typically show relative strengths in social skills, word reading, and visual short-term memory (Boudreau, 2002 ;Fidler, Hepburn & Rogers, 2006 ;Jarrold, Baddeley & Hewes, 1999) and relative weaknesses in oral language and verbal short-term memory (Abbeduto, Warren & Conners, 2007 ;Jarrold et al, 1999). Within literacy skills, individuals with Down syndrome have difficulties in nonword reading and reading comprehension in comparison to their strength in word reading (Nash & Heath, 2011 ;Roch & Jarrold, 2008) Within the oral language domain, expressive language tends to be weaker than receptive language (Laws & Bishop, 2003), and expressive vocabulary has been found to be below the level expected given nonverbal ability (Naess, Lyster, Hulme & Melby-Lervåg, 2011). suggested that the relatively intact word reading skills of children with DS may serve to promote their oral language development.…”
Section: Introductionmentioning
confidence: 99%
“…The SRep tasks target linguistic knowledge and draw on grammaticality, plausibility, prosody and lexicality (Polišenská, Chiat, & Roy, 2015). SRep has been proven to be a good clinical marker for the identification of children with language impairment in monolingual populations (Archibald & Joanisse, 2009;Conti-Ramsden, Botting, & Faragher, 2001;Laws & Bishop, 2003;Redmond, Thompson, & Goldstein, 2011). This is due to the test's high sensitivity and specificity.…”
Section: Sentence Repetition Taskmentioning
confidence: 99%
“…Reading is a critical skill for individuals with learning disabilities as it may open up vocational opportunities, facilitate increased independence and help improve language and communication skills (Buckley, 1985). The cognitive profile observed in DS is typically uneven with language ability being more affected than nonverbal ability (e.g., Laws & Bishop, 2003) and reading accuracy (Cardoso Martins, Peterson, Olson & Pennington, 2009). Most children with Down syndrome can learn to read, although levels of attainment vary considerably (Sloper, Cunningham, Turner, & Knudsen, 1990;Kay-Raining Bird, Cleave, & McConnell, 2000;Laws & Gunn, 2002).…”
Section: Introductionmentioning
confidence: 99%